Removal Of Dyes Using Citric Acid Modified Oil Palm Shell - Yuen, Mei Lian (2009)

(untitled)
This study investigates the effectiveness of using modified oil palm shell (MPS) to remove dye from solution. The feasibility of modified oil palm shell in removing basic dyes from solution was evaluated and compared with the unmodified oil palm shell (NPS). The optimized modification condition was obtained by treating 1.00 g of oil palm shell with 7 mL of 1.20 M citric acid in an oven at 120 'C for 90 minutes. The prepared adsorbent was characterized by a Scanning Electron Microscopy and Fourier Transform Infrared Spectroscopy. In each adsorption experiments, 200 mL of dye solution of known concentration and pH was added to a certain amount of adsorbent and the mixture was stirred for 4 hours. Batch studies were performed under various experimental conditions and the parameters studied include initial pH of solution, contact time on different initial dye concentrations, temperature, particle size and adsorbent dosage. The desorptibility of the adsorbent and its ability to remove other dyes were also examined. Besides that, isotherm studies were done to determine the adsorption capacity of NPS/MB, MPS/MB and MB-loaded MPS/IC systems by varying the dye concentration solutions.